Investigating the transition of psychopathological symptoms from childhood to adolescence in maltreated youth: a cross sectional study - Fucà, Elisa; Sperandini, Veronica; Falvo, Stefania; De Rose, Paola; Vicari, Stefano (Frontiers in Psychiatry, 2025)
InrtroductionThe transition to adolescence is a crucial developmental phase in which notable and significant changes in behavior may emerge. Despite child maltreatment represents one of the most critical public health risk factors for mental health disorders, poor is known about possible differences in psychopathological symptoms between children and adolescents who experienced maltreatment. Using a cross-sectional, multi informant approach, this study had three objectives: (i) to examine age-related differences in psychopathological symptoms in maltreated children and adolescents using a multi-informant, cross-sectional approach, (ii) to investigate sex differences in psychopathological symptoms across age groups, and (iii) to assess differences in adaptive skills based on age and sex.MethodsOne hundred and ninety-five youth with a history of maltreatment (6–17 years) were included. Psychopathological symptoms were assessed by caregiver- reports, self-reports and by a clinician’s rating scale, whereas adaptive skills were assessed by the Adaptive Behavior Assessment System.ResultsParent-reports and evaluation of adaptive skills highlighted a worse social functioning in adolescents in comparison with children. These findings were corroborated by self-reports. Both parent- and self-reports, but not clinician’s ratings, revealed some sex differences, with school-age girls exhibiting more parent-reported somatic complaints and male adolescents exhibiting more parent-reported aggressive behaviors. Moreover, female adolescents displayed more self-perceived ineffectiveness and interpersonal difficulties.DiscussionOverall, these findings indicate deficits in adaptive functioning within the social domain of maltreated children and adolescents, highlighting the critical need for a deeper exploration of these impairments, as disrupted social functioning during adolescence may further impede their development and integration into society. These findings underscore the need for targeted clinical interventions to address the worsening social adaptation in this population.